Enhancing nanofiltration desalination performance using air sparging technique - Saleh, Faaiz Hussain; Al-Alawy, Ahmed Faiq; Al-Salihi, Sara (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Concentration polarization is a critical problem for nanofiltration membranes, as it reduces permeate flux and increases operating costs. This study aims to assess the efficacy of air spraying technology as an innovative approach to enhance nanofiltration membrane performance, specifically in water treatment. The methodology focused on conducting comprehensive trials using simulated water and on implementing air-spraying technology at flow rates ranging from 1.5 to 4.5 liters per minute. The membrane's performance was tested under a range of conditions, including varied input concentrations (2,000 to 15,000 ppm), pressures (4 to 6 bar), water flow rates, and temperatures (20 and 32°C). The results showed that adding air efficiently reduces concentration polarization, thereby significantly increasing permeate flux and the effectiveness of sodium chloride rejection. At 2,000 ppm and 6 bar, the most significant flow was 168 liters/h, with a rejection ratio of 90.8%. The highest achievable flux was likewise reached at 32°C, with an excellent rejection ratio of 91.75%. The study, on the other hand, indicated that increasing the feed concentration worsened the permeability flux. This study demonstrates that air-spraying technology is an effective means of improving nanofiltration membrane performance.